2022
DOI: 10.1101/2022.07.01.498487
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complement receptor C5aR1 signaling in sensory neuron-associated macrophages drives neuropathic pain

Abstract: Neuroimmune interactions across the pain pathway play a predominant role in the development of neuropathic pain. Previous reports demonstrated that complement driven effector systems including the C5a/C5aR1 axis contribute to these neuro-immune mechanisms. However, the cellular and molecular mechanisms underlying C5a/C5aR1 signaling-mediated neuropathic pain development remain ill-identified. Here we show that neuropathic pain following peripheral nerve injury was attenuated in C5aR1-deficient male and female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…C5a has been implicated in various pain conditions, including post-operative 16 , in ammatory 17 , and neuropathic pain 24 . To date, although little is known about the association between the complement system components and endometriotic pain, uctuation of C5a plasma levels during the different disease stages of endometriosis has been documented in female patients 20,40 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…C5a has been implicated in various pain conditions, including post-operative 16 , in ammatory 17 , and neuropathic pain 24 . To date, although little is known about the association between the complement system components and endometriotic pain, uctuation of C5a plasma levels during the different disease stages of endometriosis has been documented in female patients 20,40 .…”
Section: Discussionmentioning
confidence: 99%
“…A considerable proportion of women with endometriosis-associated pain reported a neuropathic-like pain component 41 . Recently, it has been observed that neuropathic-like pain caused by peripheral nerve injury in mice was modulated by activation of neuron associated C5aR1+ macrophages 24 . In our study, results obtained with the C5aR1 inhibitor and transgenic MaFIA mice con rm that increases in plasma C5a and nerve trunk macrophages are essential for the development of endometriosis-associated pain-like responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations